Private Infrastructure : Emerging Market Sponsors Dominate Private Flows - Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
Investment flows to infrastructure projects with private participation in developing countries grew by 12 percent to US$64 billion in 2004. Telecommunications investments drove the growth, rising by 35 percent, while investment flows to other infrastructure sectors fell by 20 percent. Greenfield projects were the most common type of private participation, and management contracts became more frequent.